Efficacy of gamma knife radiosurgery in the treatment of intraventricular meningiomas. (October 2020) - Samanci, Yavuz; Oktug, Defne; Yilmaz, Meltem; Sengoz, Meric; Peker, Selcuk
Highlights: Meningiomas are rather rare in the ventricular system. GKR for IVMs seems to be a safe and effective primary option with low morbidity. GKRS can be considered an alternative to re-surgery for residual /recurrent tumors. Abstract: Intraventricular meningiomas (IVMs) are notably limited tumors and express one of the most challenging tumors in neurosurgery. Gamma Knife radiosurgery (GKRS) as an alternative for IVMs has been reported only in a few case series. We aimed to present six patients with IVMs who were treated with GKRS and do a literature review. The data of patients were retrospectively reviewed. All patients underwent a single session of GKRS with a median marginal dose of 12 Gy (range, 11–13). Target volume ranged from 1.2 to 9.5 cc. Routine imaging with contrast-enhanced MRI scans was performed every six months initially and thereafter yearly. New neurological deficits and symptoms stated or observed during follow-up were recorded and investigated. The mean age was 41.3 years (range, 30–71). GKRS was used as a primary treatment in five patients and as adjunctive treatment in one patient. The most common presenting symptom was a headache. The median duration of symptoms was 30 months (range, 5–240). Four tumors (67%) were located in the left lateral ventricle, and two were in the right lateral ventricle. During a median follow-up of 71.5 months (range, 23–139), tumor volume was noted to have shrunk (median = 59.6%) in all patients (100%). One patient experienced post-GKRS peritumoral edema that resolved after a short course of steroids. The mean progression-free survival was 117.5 months (95% CI, 81–154 months). Neurologic symptoms and signs improved in all patients. GKRS may be a feasible treatment alternative in patients with small IVMs with low morbidity.